Indications for treatment of rapid palatal expansion devices based on cone-beam computed tomography - A. A. Smirnova; O. A. Gavrilova; E. V. Motornova; I. I. Mikhaleva; K. V. Fedorova; L. N. Sokolova (Эндодонтия Today, 2022)
Currently, many orthodontists often prescribe the method of rapid palatal expansion (RPE) to patients, however, there are no clear criteria for indications for the use of the method based on cone-beam computer tomography (CBCT) in the available literature.Aim. Determination of indications for the use of the technique of rapid palatal expansion based on the data of the CBCT.Materials and methods. A retrospective analysis of control and diagnostic models and CBCT of 40 patients with diagnosed narrowing of the upper jaw was carried out. All the subjects were divided into two groups: the first was patients who were treated with RPE devices. The second is patients whose orthodontic treatment used other methods (mainly expanding removable plate apparatus or partial bracket system). The analysis of control and diagnostic models according to the Pona method and the determination of palate narrowing by CBCT were carried out. Comparison of the two groups by a quantitative indicator having a normal distribution, provided that the variances were equal, was performed using the Student's t-test, with unequal variances – Welch's t-test. The comparison of the two groups by a quantitative indicator, the distribution of which differed from the normal one, was carried out using the Mann-Whitney U-test.Results. Analysis of measurements in the area of premolars and molars by the Pona method in both groups revealed no statistically significant differences (p = 0.093, p = 0.137, respectively). However, when analyzing the indicators obtained by measuring the width of the palate at the level of the deepest points of the bone base in the projection of the Pon line, it showed the presence of statistically significant differences (p < 0.001). The following values were obtained: the average width of the palate at the molar level in patients using the RPE method was 24± 2 mm, in the second group – 30± 2 mm. At the premolar level, the average width of the palate in patients treated with the RPE method is 20 mm, in group 2–22 mm.Conclusions. With a narrowing of the palate less than 26 mm at the level of the molars and less than 20 mm in the premolar region, the use of methods of rapid palatal expansion can be shown. Further development of the methodology and indications for treatment with rapid palatal dilation devices is required.